2014
DOI: 10.1016/j.molcel.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Drug Sensing by the Ribosome Induces Translational Arrest via Active Site Perturbation

Abstract: SUMMARY During protein synthesis, nascent polypeptide chains within the ribosomal tunnel can act in cis to induce ribosome stalling and regulate expression of downstream genes. The Staphylococcus aureus ErmCL leader peptide induces stalling in the presence of clinically important macrolide antibiotics, such as erythromycin, leading to the induction of the downstream macrolide resistance methyltransferase ErmC. Here, we present a cryo-electron microscopy (EM) structure of the erythromycin-dependent ErmCL-stalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
178
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(188 citation statements)
references
References 32 publications
8
178
2
Order By: Relevance
“…Recent structural studies revealed that out of the C-terminal amino acids of the stalled nascent peptide, residues −8 to −2 (if the C-terminal residue is assigned position number 0) are in close proximity to the NPET-bound macrolide antibiotic (14,20). Consequently, we anticipated that this segment of the nascent polypeptide chain that interacts with the drug would define the sites of macrolide-induced ribosome stalling.…”
Section: Resultsmentioning
confidence: 99%
“…Recent structural studies revealed that out of the C-terminal amino acids of the stalled nascent peptide, residues −8 to −2 (if the C-terminal residue is assigned position number 0) are in close proximity to the NPET-bound macrolide antibiotic (14,20). Consequently, we anticipated that this segment of the nascent polypeptide chain that interacts with the drug would define the sites of macrolide-induced ribosome stalling.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the structures of EVN and AVI on the ribosome, we prepared Erm-stalled ribosome complexes (SRCs) as reported (25,26). The SRCs were incubated with either 100 μM EVN or AVI, and the complexes were then subjected to singleparticle cryo-EM analysis (Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…The SRCs were prepared essentially as described (25,44). Cryo-EM data collection was performed on the Titan Krios (FEI) 300-kV TEM equipped with a Falcon II direct electron detector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are integral parts of regulatory nascent polypeptides that monitor cellular physiology by undergoing regulated translational arrest (10,11). Arrest sequences interact with the ribosomal components at the peptidyl transferase center and/or the exit tunnel to interfere with the peptidyl transfer, translocation, or termination functions of the ribosome (12)(13)(14)(15). They are diverse in length and primary sequences; translation arrest is either inducible with a specific small molecule or is intrinsic but is subject to release by a physical pulling force that is applied to the nascent chain (10,16,17).…”
mentioning
confidence: 99%